The Value of an Empirical Approach for the Assessment of Diatoms as Environmental Trace Evidence in Forensic Limnology. (2nd December 2016) - Scott, Kirstie; Morgan, Ruth; Jones, Vivienne; Dudley, Aoife; Cameron, Nigel; Bull, Peter
Abstract : Environmental trace evidence is often encountered during a forensic investigation and is acknowledged to have the potential to contribute valuable circumstantial information pertaining to the context of an individual criminal event. Although traditional study has focused upon the analysis of terrestrial soil and sediment traces, there is growing potential for the forensic assessment of aquatic crime scenes, particularly those within freshwater environments. This paper outlines the current applications of limnology, particularly algae and diatom analysis, within forensic science and introduces new and ongoing research within the field. Two empirical studies are presented which highlight the importance of developing evidence bases within freshwater trace evidence analysis. These studies demonstrate the analytical capability of the Scanning Electron Microscope (SEM) at various stages of an investigation: in the initial screening and collection of an evidential sample from clothing (1); and in the analysis of preserved diatoms following various levels of their exposure to fire damage (2). The results highlight that the SEM provides a valuable tool during the initial stages of an investigation, determining the presence and abundance of a range of environmental indicators and directing further strategy for the more in-depth collection and analysis of a forensic sample. Furthermore, the preservation of diatoms adhering to clothing following prolonged exposure to fire, indicates that efforts to collect any destroyed evidence are worthwhile given the potential to recover freshwater traces over extended time scales. Finally, the value of adopting an empirical approach for the development of a forensically relevant evidence base within forensic limnology, and the importance of having an appreciation of the legal implications for the interpretation and admissibility of freshwater evidence is presented.